2016
DOI: 10.1113/jp272491
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria‐specific antioxidant supplementation does not influence endurance exercise training‐induced adaptations in circulating angiogenic cells, skeletal muscle oxidative capacity or maximal oxygen uptake

Abstract: Antioxidants have been shown to improve endothelial function and cardiovascular outcomes. However, the effects of antioxidants on exercise training-induced vascular adaptations remain elusive. General acting antioxidants combined with exercise have not impacted circulating angiogenic cells (CACs). We investigated whether mitochondria-specific antioxidant (MitoQ) supplementation would affect the response to 3 weeks of endurance exercise training on CD3 , CD3 /CD31 , CD14 /CD31 , CD31 , CD34 /VEGFR2 and CD62E pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 69 publications
5
43
0
1
Order By: Relevance
“…The use of mitochondrial specific antioxidants is a step forward for controlling oxidant activity in specific cellular compartments without drastically affecting overall cellular redox state, different cellular functions and muscle adaptation to exercise (Shill et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of mitochondrial specific antioxidants is a step forward for controlling oxidant activity in specific cellular compartments without drastically affecting overall cellular redox state, different cellular functions and muscle adaptation to exercise (Shill et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…glucose uptake, Sandström et al 2006; force development, Andrade et al 1998; and adaptation to exercise training, Kavdia, 2011), the use of antioxidants supplementation needs to be well deliberated to avoid blunting of ROS signalling. The use of mitochondrial specific antioxidants is a step forward for controlling oxidant activity in specific cellular compartments without drastically affecting overall cellular redox state, different cellular functions and muscle adaptation to exercise (Shill et al 2016).…”
Section: The Extracellular P O2 May Impact the Effects Of Ss31 On Plffdmentioning
confidence: 99%
“…Although there is a large amount of evidence to suggest that MitoQ administration provides beneficial effects, recent studies in the field of muscle metabolism have shown that MitoQ was found to have no effect on exercise-induced adaptations in muscle oxidative capacity in humans. 308 Similarly, in the context of musculoskeletal ageing, MitoQ intervention in old mice failed to rescue the loss of muscle mass and function associated with ageing of skeletal muscle. 39 Overall, targeted antioxidant compounds such as SS-31 and MitoQ are clearly useful from a mechanistic perspective; however, the ability to translate these findings in a human context remains less clear.…”
Section: Neuron-specific Reduction Of Cuznsod Is Not Sufficient To Inmentioning
confidence: 99%
“…Increases in fat mass, manifested as an increase in white adipose tissue (WAT), increases oxidative stress/oxidant production and results in an obese phenotype [11] characterized by a BMI (Body Mass Index) ≥ 30kg/m 2 [12]. The obese phenotype is accompanied by mitochondrial dysfunction and increased lipid peroxidation in adipose tissue, further leading to the dysfunction of other metabolic tissues such as liver, muscle, [11, 13] gut, and brain [14]. …”
Section: Introductionmentioning
confidence: 99%